Genetic diversity and population structure of the Sapsaree, a native Korean dog breed - Gajaweera, Chandima (BMC Genet, 2019)
BACKGROUND: The Sapsaree is a breed of dog (Canis familiaris) native to Korea, which became perilously close to extinction in the mid-1980s. However, with systematic genetic conservation and restoration efforts, this breed was rescued from extinction and population sizes have been gradually increasing over the past few decades. The aim of this study was to ascertain novel information about the genetic diversity, population structure, and demographic history of the Sapsaree breed using genome-wide single nucleotide polymorphism data. We characterized the genetic profile of the Sapsaree breed by comparison with seven foreign dog breeds with similar morphologies to estimate genetic differentiation within and among these breeds. RESULTS: The results suggest that Sapsarees have higher genetic variance compared with the other breeds analyzed. The majority of the Sapsarees in this study share a discrete genetic pattern, although some individuals were slightly different, possibly as a consequence of the recent restoration process. Concordant results from analyses of linkage disequilibrium, effective population size, genetic diversity, and population structural analyses illustrate a relationship among the Sapsaree and the Tibetan breeds Tibetan terrier and Lhasa Apso, and a small genetic introgression from European breeds. The effective population size of the Sapsaree has contracted dramatically over the past generations, and is currently insufficient to maintain long-term viability of the breed’s genetic diversity. CONCLUSIONS: This study provides novel insights regarding the genetic diversity and population structure of the native Korean dog breed Sapsaree. Our results suggest the importance of a strategic and systematic approach to ensure the genetic diversity and the authenticity of the Sapsaree breed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12863-019-0757-5) contains supplementary material, which is available to authorized users.